PENGAMPUNAN SEBAGAI WUJUD INKARNASI KRISTUS: DASAR TEOLOGIS BAGI PEMULIHAN JIWA MANUSIA YANG TERLUKA - Deni Leyden Waljufri (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2025)
This research explores the relationship between forgiveness as a manifestation of Christ's incarnation and the healing of the wounded soul, a topic often overlooked in theological and pastoral discourse. Employing a qualitative approach combining systematic theology and field-based phenomenology, this paper analyzes the theological foundation of Christ's incarnation as the basis for divine love and solidarity with human suffering. Forgiveness, made possible by Christ's redemptive work, is understood as a restorative act transcending its legalistic aspect, aiming to restore damaged identity, dignity, and relationships. Empirical findings from narratives of individuals experiencing inner wounds consistently demonstrate that forgiveness is a primary catalyst for healing. Cases such as liberation from possession, recovery from physical ailments (acid reflux), and self-forgiveness overcoming insomnia consistently affirm the transformative impact of forgiveness. Conversely, the refusal to forgive proves to be a serious barrier to healing. The discussion integrates these findings, asserting that soul healing is an integral part of Christ's holistic mission, and its pastoral implications highlight the church's urgency in implementing a comprehensive theology of forgiveness. This research contributes to theological and practical discourse, offering a framework for more effective and Christ-centered soul recovery ministries